Comparison of Ephedrine and Dopamine to Manage Hypotension and Assessment of Arterial Pressure Waveform Analysis to Monitor Cardiac Ouput in Dogs Under Isoflurane Anesthesia - Hui, Cheng Chen (2004)
The first study compared the cardiovascular responses of ephedrine at 0.2 mg/kg, IV (doubled to 10µg/kg/min, IV, if inadequate response) to manage hypotension in clinical canine cases during routine anesthetic management. Treatments were randomly assigned to treat hypotension (mean arterial pressure, MAP < 60 mm Hg) in 12 cases. When MAP remained lower than 70 mm Hg at 10 minutes post treatment, the ephedrine bolus was repeated or the dopamine infusion was doubled. The pressure-elevating effect of ephedrine was found to last less than 5 minutes, with improvement in cardiac index (CI), stroke volume index (SVI) and oxygen delivery index (DO2I), but a decrease in systematic vascular resistance (SVR) at 10 minutes. Repeating the ephedrine did not produce further improvement. The infusion of dopamine at 5µg/kg/min did not improve blood pressure (BP), CI, DO2I or SVI within 10 minutes. Increasing the infusion to 10µg/kg/min improved BP within 5 minutes, and increased CI, DO2I and SVI by 10 minutes. The ephedrine boluses were less effective than the dopamine infusions to augment BP, but the improvement in CI, DO2I and SVI by the end of the 20 minute study period was not different between treatments.